Rural settlement within the hinterland of conurbations - Harper, S; Harper, Sarah (1985)
The post war years have seen a steady flow of inmigration into the rural hinterlands of conurbations, eminating both from the surrounding rural areas and from the urban complexes themselves. By 1981 over one fifth of Britain's population was resident in a rural district, the majority falling within zones close to urban centres. This study, based on one year's participant observation in seven settlements within southern Staffordshire, part of the rural hinterland of the West Midlands Conurbation, and southern Hampshire, adjacent to the Southampton - Portsmouth axis, the South Hampshire Conurbation, assess this process. Using the technique of Cluster Analysis, three broad groupings of settlement are identified: the small agricultural settlement, the urbanised commuter village, and settlements in a process of transition between the two. The development of the case settlements, representatives of these three groupings, is assessed in relation to their historical and geographical context, with emphasis being placed on land tenure and local planning policy. An analysis is undertaken of the "hinterland population", the diverse populations now resident within the rural hinterlands. Nine broad groupings emerge from this population, identifiable with reference to socio-economic characteristics and ways of life, and these are examined in relation to their use, their environments, social networks and patterns of behaviour, and perceptions of their place of residence. These groups are represented in various proportions within each settlement type, in relation to the dominant housing class found there. As a result a variety of community forms are seen to be developing, with a polarisation of settlements along class lines. Running concurrently with this, two theoretical concepts are introduced based on the approach of Symbolic Interactionism. These are the Triadic Relationship, and Place Centredness, which provide a more humanistic framework for the analysis. The inclusion of these concepts enables an assessment to be made of the notions of "rurality" and "truly rural population".